A method for detecting heat resistance of polyimide substrate
By etching specific lines on the polyimide substrate and performing cooking and hot and cold impact testing, the test results deviation caused by half-etching of metal layer in the existing test methods is solved, and more accurate heat resistance detection is achieved.
Patent Information
- Application Number
- CN202110497546.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-05-07
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2041-05-07
AI Technical Summary
The existing polyimide substrate heat resistance testing methods are completely etched away when etching the metal layer, resulting in a bias in the test results.
By adopting a polyimide substrate heat resistance detection method, the test sample and the comparison sample are cut on the polyimide substrate, and the corrosion resistance tape is applied at predetermined line intervals on the first metal layer. During the etching process, only the metal parts not covered by the corrosion resistance tape are etched to form the shape of a specific line, and then steaming and hot and cold impact tests are carried out.
This method can more accurately detect the heat resistance of the polyimide substrate, prevent the explosive layering phenomenon caused by water absorption, and improve the accuracy of the test.
Smart Images

Figure CN114764055B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of polyimide materials, and in particular to a method for detecting heat resistance of a polyimide substrate. Background Art
[0002] Polyimide refers to a class of polymers containing an imide ring (-CO-N-CO-) on the main chain. It is one of the organic polymer materials with the best comprehensive performance. As a special engineering material, polyimide has been widely used in aviation, aerospace, microelectronics, nano, liquid crystal, separation membrane, laser and other fields. The existing common polyimide material has a dielectric constant of 4.0-4.5, a dielectric loss of 0.010-0.020, and a test frequency of 10GHz. At present, polyimide substrates need to withstand a certain amount of heat when using solder paste. If the substrate has poor heat resistance, delamination, blistering and other undesirable phenomena will occur, which will directly lead to circuit breaks between layers and the circuit board cannot be used.
[0003] In the existing heat resistance test method, half of the metal layer of the polyimide substrate is completely etched away during the test before subsequent testing. This test method is likely to cause deviations in the test results. Summary of the invention
[0004] The present invention provides a method for detecting the heat resistance of a polyimide substrate, which can solve one or more of the above-mentioned problems in the prior art.
[0005] According to one aspect of the present application, a method for detecting heat resistance of a polyimide substrate is provided, comprising the following steps:
[0006] (1) Prepare polyimide substrate:
[0007] The polyimide substrate includes a first metal layer, a substrate layer and a second metal layer in sequence; two groups of test samples and comparison samples of the same size are cut from the polyimide substrate, the second metal layer of each of the test samples and comparison samples is completely covered with an anti-corrosion tape, and the first metal layer is covered with an anti-corrosion tape according to a predetermined circuit interval;
[0008] (2) Etching: etching the prepared test sample and comparison sample until the first metal layer of the test sample and comparison sample not affixed with the anti-corrosion tape is completely etched and then drying and keeping warm;
[0009] (3) Steaming: After the drying and heat preservation, the control sample and the test sample are taken out, cooled to room temperature, and then steamed;
[0010] (4) Thermal shock test: placing the test sample into the solder bath liquid surface, keeping the test sample in contact with the solder bath liquid surface; taking out the test sample after cooling to room temperature to obtain the thermal shock;
[0011] Determine whether the test sample is qualified after hot and cold shock.
[0012] In some embodiments, the qualified conditions of the test specimen after thermal shock include:
[0013] The surface condition of the test specimens after thermal shock is satisfactory; and
[0014] Conduct bonding strength tests on the circuit side of the control sample and the test sample after hot and cold shock respectively and judge whether the test results are qualified; and
[0015] Take the test sample obtained after the hot and cold shock, take part of the sample on the circuit that has not been etched for cross-section sampling, and then make slices to observe whether it is qualified.
[0016] In some embodiments, the surface condition of the test specimen after the thermal shock is qualified as follows: there is no blistering and delamination on the surface.
[0017] In some embodiments, the bonding strength test of the control sample and the test sample after the thermal shock on the circuit side includes the following steps:
[0018] The bonding strength between the metal layer and the substrate of the comparison sample and the test sample is tested with a universal tensile machine on the side with circuits, and recorded as f1 and f2 respectively. If (f1-f2) / f1≤5%, it is qualified, otherwise it is unqualified.
[0019] In some embodiments, the method for making slices includes: mixing acrylic powder and a curing agent into a solution, placing the sample for cross-section sampling into the solution, hardening at room temperature and polishing it smooth with sandpaper.
[0020] In some embodiments, the size of the control sample and the test sample is: (50.8±0.75) mm×(50.8±0.75) mm.
[0021] In some embodiments, the method of coating the first metal layer with an anti-corrosion tape at a predetermined line interval includes:
[0022] Use 3.18mm wide anti-corrosion tape to paste 3 strips, with a spacing of 10mm between each strip.
[0023] In some embodiments, the first metal layer and the second metal layer are both copper foils.
[0024] In some embodiments, the material of the resist tape is PET.
[0025] In some embodiments, the etched comparative sample and the test sample are kept in an oven at 125±2° C. for 4-6 hours, taken out, and cooled to room temperature in a desiccator.
[0026] In some embodiments, the cooking is performed in a pressure cooker for 1 hour, and the pressure is maintained at 103.5±3.5 KPa.
[0027] Compared with the prior art, this application has the following beneficial effects:
[0028] In the sample processing method of the present application, the second metal layer is completely covered with an anti-corrosion tape, and the first metal layer is covered with an anti-corrosion tape according to a predetermined circuit interval. Then, during the etching process, only the metal part not covered by the anti-corrosion tape, that is, the exposed part, will be etched away, that is, it is made into a shape containing part of the specific circuit. Then, it is boiled and water is absorbed, and then hot and cold shocks are performed. This can prevent the outflow of the board due to the long exposure time of the substrate on site and the absorption of water, which leads to the bursting and delamination of the board.
[0029] The substrate will absorb water molecules after cooking. When heated, the water molecules will be released from the pores of the substrate molecules. If the amount of water absorbed is large, the large amount of water molecules released suddenly may bulge when encountering the copper foil barrier, resulting in poor delamination of the substrate.
[0030] The present application processes the test sample to make a model with intervals of copper foil, without copper foil, and with copper foil, and then absorbs water through steaming. If the amount of water absorbed is large, when subjected to hot and cold shock, whether the copper foil left on the surface of the sample will delaminate from the substrate or other undesirable phenomena can be better reflected, thereby increasing the accuracy of the heat resistance test. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 A schematic cross-sectional view of a polyimide substrate according to one embodiment of the present invention
[0032] Figure 2 It is a cross-sectional schematic diagram of a polyimide substrate coated with a spacer and a resist tape according to one embodiment of the present invention;
[0033] Figure 3 for Figure 2 A schematic cross-sectional view of a polyimide substrate after the exposed metal portion has been etched;
[0034] Figure 4 It is a cross-sectional schematic diagram of a polyimide substrate half of which is covered with an anti-corrosion tape in the prior art;
[0035] Figure 5 for Figure 4 Schematic diagram of the cross section of the polyimide substrate after the exposed metal part is etched;
[0036] Figure 6 It is a schematic cross-sectional view of a polyimide substrate coated with a spacer and a resist tape according to one embodiment of the present invention. DETAILED DESCRIPTION
[0037] The present invention will be further described in detail below with reference to the accompanying drawings and embodiments.
[0038] Example 1 Test Example
[0039] like Figure 1 As shown, a method for detecting heat resistance of a polyimide substrate comprises the following steps:
[0040] (1) Prepare polyimide substrate:
[0041] like Figure 1 As shown, the polyimide substrate includes a first metal layer, a substrate layer and a second metal layer in sequence. Two groups of test samples and comparison samples of the same size are cut out on the polyimide substrate. Each group of test samples and comparison samples has 3 pieces. The size of each sample is approximately (50.8±0.75) mm×(50.8±0.75) mm.
[0042] like Figure 2 and Figure 6 As shown, whether it is a test sample or a comparison sample, on each sample, the second metal layer 103 is completely covered with an anti-corrosion tape 104 of the same specification, and the first metal layer 101 is covered with an anti-corrosion tape 104 of the same specification according to a predetermined line interval. Optionally, the first metal layer 101 and the second metal layer 103 are generally made of copper foil, and the substrate layer 102 is generally made of a composite material of resin and glass fiber cloth. The anti-corrosion tape 104 is generally made of PET (polyethylene terephthalate). Figure 1 As shown, the first metal layer 101 on each sample can be pasted with 3 strips of PET anti-corrosion tape, with a spacing of 10 mm between each strip. Of course, the coating method of the anti-corrosion tape 104 can also be designed according to actual needs.
[0043] (2) Etching: Etching the prepared test sample and comparison sample until the first metal layer of the test sample and comparison sample that is not affixed with the anti-etching tape, i.e., the exposed portion, is completely etched. Figure 3 As shown. Figure 6 The schematic diagram shows that the strips 1, 2, and 3 are the copper foils that were originally covered by the anti-etching tape but not etched away. Generally, etching is done by soaking the sample in 31% hydrochloric acid, cleaning the edges of the comparison sample and the test sample after etching, polishing them with sandpaper, keeping them in an oven at 125±2℃ for 4-6 hours, and cooling them to room temperature in a dryer after taking them out. The cross-sectional view after etching is shown in the figure below. Figure 3 shown.
[0044] (3) Cooking: The control sample and the test sample in step (2) are taken out and placed in a pressure cooker for cooking for 1 hour, with the pressure maintained at 103.5±3.5 KPa; taken out from the pressure cooker, rinsed with clean water, and wiped off the moisture on the surface with a dust-free cloth.
[0045] (4) Hot and cold shock test: Only the test sample group needs to be subjected to hot and cold shock test, while the control sample group does not need to be subjected to hot and cold shock test. Specifically, in order to protect the test sample when it is taken out of the tin bath, a layer of talcum powder can be applied to the surface of the test sample and then placed in a solder bath at a temperature of 288±5.5℃. Float soldering is performed for 10+1 / -0s, and the test sample is kept in direct contact with the solder surface. Use a pliers-like tool to gently press down to stir the solder. Take it out and cool it to room temperature.
[0046] (5) Test sample result judgment:
[0047] a. After the hot and cold shock, visually inspect the test specimens for obvious blistering, delamination, and other damage, and record the results.
[0048] b. Use a universal tensile machine to test the bonding strength between the copper foil and the substrate on the side with the circuit on the comparison sample and the test sample, and record them as f1 and f2 respectively. (f1-f2) / f1≤5% is qualified, and greater is unqualified.
[0049] c. Figure 1 As shown, positions A, B, and C are cut off on the test sample, and cross-sections are taken from positions A, B, and C for slicing. The method for making the slicing comprises: mixing acrylic powder and a curing agent into a solution, placing the sample for cross-section sampling into the solution, hardening at room temperature, and then polishing it from coarse to fine with 400#-4000# sandpaper, observing whether there is delamination, blistering, and other damage under a microscope, and recording the results.
[0050] Example 2 Comparative Example of Existing Method
[0051] (1) Sample preparation:
[0052] The same metal foil-clad laminate as in Example 1 was cut into 3 pieces of size (50.8±0.75) mm×(50.8±0.75) mm. Figure 4 As shown, half of each laminate is covered with a resist tape before etching. Figure 5 As shown, half of each sample is completely etched away from the metal foil, and the edge of the sample should be cleaned and polished with sandpaper to a smooth state; then it is kept in an oven at 125±2℃ for 4-6h, and then taken out and cooled to room temperature in a desiccator.
[0053] (2) Sample measurement
[0054] Take out the sample from the dryer, keep the sample at the solder tank liquid level of 288±5.5℃ for 10 minutes, float solder for 10+1 / -0s, keep the sample in direct contact with the solder surface, and stir the solder by gently pressing down with a pliers-like tool. Take the sample out of the solder and cool it to room temperature. Visually check the sample for obvious blistering, delamination and other damage. During the exposure to solder, obvious surface deterioration, such as blistering of the sample and adhesion to the fixture, should be recorded as possible signs of delamination. This process is one cycle.
[0055] That is, the difference between Example 2 and Example 1 is:
[0056] 1. The way in which the test samples in Example 1 and Example 2 are coated with the anti-corrosion tape is different;
[0057] 2. Example 2 is not cooked;
[0058] 3. Example 2 is not judged by sectioning observation.
[0059] Except for the above three points, the detection conditions of Example 2 are the same as those of Example 1.
[0060] The specific test results of Example 1 and Example 2 are compared as shown in Table 1 below:
[0061] Table 1 - Comparison of test results
[0062]
[0063]
[0064] Comparing the two groups of examples, the bonding strength of the test samples using the present invention decreased significantly, and two test samples had bubbles when observed by slicing, which was judged as NG. This shows that if the existing method is used for testing, all of them are OK, and defective products may flow to the client.
[0065] Compared with the prior art, this application has the following beneficial effects:
[0066] In the sample processing method of the present application, the second metal layer is completely covered with an anti-corrosion tape, and the first metal layer is covered with an anti-corrosion tape according to a predetermined circuit interval. Then, during the etching process, only the metal part not covered by the anti-corrosion tape, that is, the exposed part, will be etched away, that is, it is made into a shape containing part of the specific circuit. Then, it is boiled and water is absorbed, and then hot and cold shocks are performed. This can prevent the outflow of the board due to the long exposure time of the substrate on site and the absorption of water, which leads to the bursting and delamination of the board.
[0067] The substrate will absorb water molecules after cooking. When heated, the water molecules will be released from the pores of the substrate molecules. If the amount of water absorbed is large, the large amount of water molecules released suddenly may bulge when encountering the copper foil barrier, resulting in poor delamination of the substrate.
[0068] This application processes the test sample to make a model with equal intervals of copper foil-no copper foil-copper foil, and then boils it to absorb water. If the amount of water absorbed is large, when performing hot and cold shocks, whether the copper foil left on the surface of the sample will delaminate with the substrate and other undesirable phenomena can be better reflected, thereby increasing the accuracy of the heat resistance test. Moreover, this method of using anti-corrosion tape to make specific circuits is closer to the client's usage. After boiling and then performing hot and cold shocks, it is possible to detect the delamination of the substrate due to the rapid release of water absorbed and then subjected to hot and cold shocks, or the delamination of water molecules and certain groups in the substrate at high temperatures. This situation cannot be detected by existing detection methods. The method of making slices and then observing the inside under a microscope can eliminate the influence of human subjective factors and has better repeatability.
[0069] The above are only some embodiments of the present invention. For those skilled in the art, several modifications and improvements can be made without departing from the creative concept of the present invention, which all belong to the protection scope of the present invention.
Claims
1. A method for detecting heat resistance of a polyimide substrate, characterized in that: The following steps are involved: (1) Prepare polyimide substrate: The polyimide substrate includes a first metal layer, a substrate layer and a second metal layer in sequence; two groups of test samples and comparison samples of the same size are cut from the polyimide substrate, the second metal layer of each of the test samples and comparison samples is completely covered with an anti-corrosion tape, and the first metal layer is covered with an anti-corrosion tape according to a predetermined circuit interval; (2) Etching: etching the prepared test sample and comparison sample until the first metal layer of the test sample and comparison sample not affixed with the anti-corrosion tape is completely etched and then drying and keeping warm; (3) Steaming: After the drying and heat preservation, the control sample and the test sample are taken out, cooled to room temperature, and then steamed; (4) Thermal shock test: placing the test sample into the solder bath liquid surface, keeping the test sample in contact with the solder bath liquid surface; taking out the test sample after cooling to room temperature to obtain the thermal shock; Determine whether the test sample is qualified after hot and cold shock.
2. A method for detecting heat resistance of a polyimide substrate according to claim 1, characterized in that: The qualified conditions of the test specimen after the thermal shock include: The surface condition of the test specimens after thermal shock is satisfactory; and Conduct bonding strength tests on the side with circuits of the control sample and the test sample after hot and cold shock respectively and judge whether the test results are qualified; and Take the test sample obtained after the hot and cold shock, take part of the sample on the circuit that has not been etched for cross-section sampling, and then make slices to observe whether it is qualified.
3. A method for detecting heat resistance of a polyimide substrate according to claim 2, characterized in that: The surface condition of the test sample after the hot and cold shock is qualified as follows: there is no blistering and delamination on the surface.
4. A method for detecting heat resistance of a polyimide substrate according to claim 2, characterized in that: The bonding strength test of the comparison sample and the test sample after the hot and cold shock respectively on the circuit side includes the following steps: The bonding strength between the metal layer and the substrate of the comparison sample and the test sample is tested with a universal tensile machine on the side with circuits, and recorded as f1 and f2 respectively. If (f1-f2) / f1≤5%, it is qualified, otherwise it is unqualified.
5. A method for detecting heat resistance of a polyimide substrate according to claim 2, characterized in that: The method for making the slices comprises: mixing acrylic powder and a curing agent into a solution, placing a sample for cross-section sampling into the solution, hardening at room temperature and polishing it smooth with sandpaper.
6. A method for detecting heat resistance of a polyimide substrate according to claim 1, characterized in that: The sizes of the comparison sample and the test sample are: (50.8±0.75) mm×(50.8±0.75) mm.
7. A method for detecting heat resistance of a polyimide substrate according to claim 6, characterized in that: The method of coating the second metal layer with an anti-corrosion tape according to a predetermined circuit spacing includes: Use 3.18mm wide anti-corrosion tape to paste 3 strips, with a spacing of 10mm between each strip.
8. A method for detecting heat resistance of a polyimide substrate according to any one of claims 1 to 7, characterized in that: The first metal layer and the second metal layer are both metal copper foils, The material of the anti-corrosion tape is PET.
9. A method for detecting heat resistance of a polyimide substrate according to any one of claims 1 to 7, characterized in that: The etched comparison sample and test sample are kept in an oven at 125±2℃ for 4-6h, taken out and cooled to room temperature in a desiccator.
10. A method for detecting heat resistance of a polyimide substrate according to any one of claims 1 to 7, characterized in that: The cooking is carried out in a pressure cooker for 1 hour, and the pressure is maintained at 103.5±3.5 KPa.
Citation Information
Patent Citations
Preparation method for two-layer flexible copper clad lamination
CN104507263A
Layered polyimide / metal product
CN1750927A